Novel bi-allelic DNAH3 variants cause oligoasthenoteratozoospermia - Li, Shu; Zhang, Zexin; Xie, Linna; Zhao, Yanqiu; Chen, Hongtai; Zhang, Shijia; Cai, Yixiang; Ren, Bingjie; Liu, Wensheng; Tang, Songxi; Sha, Yanwei (Frontiers in Endocrinology, 2024)
Background Oligoasthenoteratozoospermia (OAT) is a widespread cause of male infertility. One of the usual clinical manifestations of OAT is multiple morphological abnormalities of the sperm flagella (MMAF), which are frequently associated with mutations and defects in the dynein family. However, the relationship between the newly identified Dynein Axonemal Heavy Chain 3 (DNAH3) mutation and oligonasthenospermia in humans has not yet been established. Methods Whole exome sequencing, pathogenicity analysis, and species conservation analysis of mutation sites were conducted on two patients from different unrelated families with DNAH3 mutations. We identified representative mutation sites and predicted the protein structure following these mutations. The sperm characteristics of the two patients with DNAH3 mutations were verified using Papanicolaou staining, scanning electron microscopy, and transmission electron microscopy. Additionally, mRNA and protein levels were assessed through RT-qPCR and Western blotting. Results The biallelic mutations in the first progenitor included a heterozygous deletion and insertion, c.6535_6536 delinsAC (to infect mutation (p.Asp2179Thr), and stop codon premutation, c.3249G > A (p.Trp1083Ter). In Family II, the patient (P2) harbored a DNAH3 heterozygous missense mutation, c. 10439G> A(p.Arg3480Gln), along with a stop codon premutation, (c.10260G > A; p.Trp3420Ter). Patients with premature termination of transcription or translation due to DNAH3 mutations exhibit OAT phenotypes, including fibrous sheath dysplasia and multiple tail malformations. We identified the representative sites after mutation, predicted the protein structure, and assessed changes in the protein levels of DNAH3 and related genes following mutations. Notably,a significant reduction in DNAH3 protein expression was validated in these patients. We may explore in the future how DNAH3 affects sperm motility and quality through regulatory mechanisms involving protein structural changes. Conclusion Novel biallelic mutations in DNAH3, especially those resulting in a premature stop codon, may alter protein expression, structure, and active site, leading to spermatogenic failure and potentially inducing OAT. The discovery of new mutations in DNAH3 may be the key to the diagnosis and treatment of OAT.